Effect of soil temperature during seed filling period on oleic/linoleic ratio, tocopherols and sugar contents in peanut kernels - Haro Juarez, Ricardo Javier (2020)
The relationship of chemical quality of peanut seed with the soil temperature (ST) has received little attention. The aim of this work was to determine the effects of ST in the seed growth environment, during the seed filling period, on the oleic/linoleic acid (O/L) ratio, alpha, beta, gamma, delta tocopherols and the sum of them (TT), fructose, glucose and sucrose and the sum of them (FGS), contents in peanut kernels. Field experiments included cultivars (Florman and ASEM), water regimes (irrigated and water stress), sowing dates and alteration of ST. The response of O/L ratio to ST fitted a linear model, where the O/L ratio increased while ST increased. Mean O/L ratios were 1.31 for ASEM and 1.20 for Florman. The TT mean concentration was similar for both genotypes (478 ppm). A positive association between α-tocopherol (the main source of vitamin E) and ST, and a negative association between δ and α tocopherols were detected. The responses of FGS and sucrose to ST fitted linear models, where increments in ST showed decreases in FGS and sucrose concentrations. However, the decrease rates of FGS and sucrose in ASEM were three times lower than in Florman. The results showed that ST affected the chemical composition of peanut kernels, which mainly determines the shelf life and flavor of both genotypes differentially.